2010
DOI: 10.1097/brs.0b013e3181d53b9c
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spine Stability for Subjects With and Without Low Back Pain During One-Leg Standing Test

Abstract: Although the control group included slightly younger volunteers compared with the LBP group, the stability index of the core spine significantly decreased in RHT and RST, especially when visual feedback was blocked for subjects with LBP. The interaction between visual feedback and trunk rotation indicated that core spine stability is critical in coordinating balance control. A trunk muscle imbalance may contribute to unbalanced postural activity, which could prompt a decreased, uncoordinated bracing effect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 24 publications
5
53
0
4
Order By: Relevance
“…As we hypothesized, subjects with LBP demonstrated shorter holding duration times than the control subjects. This result is consistent with other studies which concluded that the control group demonstrated better stability than the patient group [2]. Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As we hypothesized, subjects with LBP demonstrated shorter holding duration times than the control subjects. This result is consistent with other studies which concluded that the control group demonstrated better stability than the patient group [2]. Fig.…”
Section: Discussionsupporting
confidence: 93%
“…There are receptors responsible for this information which could be affected by dysfunction in the lumbar spine [7]. Accordingly, subjects with LBP may have altered postural control and balance deficits as well as reduced proprioception in the spine, which have been reported in several studies [2,3,7,8].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The method of computation was based on mathematical techniques, and kinematic joint angles were derived from the direction cosine matrices of the sensors [22,23]. The reliability of the motion analysis system has also been reported and confirmed with previous studies [2,24,26].…”
Section: Outcome Measuressupporting
confidence: 72%
“…The trunk rotations were defined as voluntary exertions, and the subjects were instructed to turn their shoulders, hips, and knees without moving their feet. They were given disposable hospital slipper socks with nonskid bottoms to wear during the test and had the Helen Hayes full body (with head) reflective marker set attached to specific sites on their bodies [24][25][26].…”
Section: Outcome Measuresmentioning
confidence: 99%